FAKTOR-FAKTOR YANG BERKORELASI TERHADAP PRODUKTIVITAS KERJA PEMETIK KOPI DI PDP KABUPATEN JEMBER - Hesti Herminingsih; Evita Soliha Hani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
The KK/Gunung Pasang Estate is the second largest estate owned by the Local Plantation Company of Jember Regency. The labour harvest of coffee productivity level is not optimal yet and the percentage of green-coffee seed is highly influential towards the realization achievement of coffee production in the  KK/Gunung Pasang Estate. For five years, the average of production realization in the KK/Gunung Pasang Estate is not optimal yet, that is only 75% target. The increasing achievement of production target can be done by optimizing the  labour harvest of coffee productivity. This research is aimed to analyze how far motivation, and ability correlate towards the labour harvest of coffee productivity by using Spearman Rank Correlation. The tools of research used correlational description. The sample method used propositional random sampling with 73 respondents. The result shown that motivation has positive correlation with the labour harvest of coffee productivity (Y). The variables of motivation include work performance (X1), and life-expectancy insurance (X3) has positive and significant correlation with the work productivity of coffee reapers. The variable responsibility (X2), and family members (X4) does not have a significant correlation with the  labour harvest of coffee productivity. Moreover, the test of age variable (X5) has positive correlation with the the  labour harvest of coffee productivity. Meanwhile, the experience variable (X6) does not have significant correlation. Keywords: Motivation,  Ability, Labour Productivity.